Training in Logistics Management and Social Media Marketing for Small, Micro and Medium Enterprises in Bekasi Regency - Richard Jokhu, Jean; Rahmiati, Filda; Hanafiah, Hally; Daniela, Lerissa; Lampatar, Jonathan; Hariri Bakri, Mohammed; Prayoga, Tasya Zahwa (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: The community service held in Cikarang district was to develop local small and medium enterprises (SMEs) in Cikarang District and to develop ambidextrous skills in social media literacy and logistic management. The recent disruption called the COVID-19 pandemic swallowed all business in Indonesia. Many small businesses have to survive in the post-pandemic era. Conventional transactions are no longer viable in the new 4.0 industry.  Contribution: Training is necessary to improve the small and medium enterprises adopting the new industry revolution. Social media and logistics are two types of skills that are crucial for all SMEs if they want to survive with the current system. We provide the integration in understanding the logistics and social media as both production and marketing tools. Method: Based on the short survey, this workshop is very important to help local SMEs. We provide the participant with material, in-house training, and more in the workshop. We also provide a WhatsApp group for free consultation for further questions like permits, logistic analysis, and SME events.  Results: Based on the feedback and the participant's responses in the workshop, They hope to have another training to develop their business into a more efficient and agile business for competition. Conclusion: Logistics and social media prowess are the two most important skills SMEs need to improve their business locally before going into a bigger pond.